Two new endemic species of Caraipa (Calophyllaceae) from the Central Amazon Basin, Amazonas State, Brazil - Cabral, Fernanda Nunes; Bittrich, Volker; Amaral, Maria Do Carmo Estanislau Do (Phytotaxa, 2017)
Two new species of Caraipa (Calophyllaceae) are described and illustrated: Caraipa glabra and C. iracemensis. Both species are known only from the municipality of Presidente Figueiredo, Amazonas state, Brazil. They both occur on patches of white-sand vegetation and they are locally abundant. Caraipa glabra is a small tree and can be distinguished from other Caraipa species by the complete absence of hairs on the leaf lamina, pedicel and fruits. Caraipa iracemensis is morphologically similar to C. grandifolia and C. caespitosa, and can be distinguished by its habit, leaves and petiole size, as well as fruit surface and size.